Clinical audit: a necessity or a formality? - Ajaz, Sami; Ahmad, Muhammad; SARFRAZ, RAZA (Journal of the Pakistan Medical Association, 2023)
Dear Editor, Clinical auditing is a widely accepted practice world wide to assess the quality of health care given by a provider (1). It is described as a quality improvement approach that aims to enhance patient care and outcomes by systematically examining of treatment against stated criteria and implementing change (2). A clinical audit provides a service with the capacity to identify deficiencies, areas of excellence, and generate relevant suggestions that would drive change. It enhances the practice of evaluating against established standards (1). In developed countries, it is an essential component of clinical practice; nevertheless, it has yet to achieve equal status in developing countries. As a result, the demand for a structured Clinical Audit program is long overdue. Surprisingly, a thorough online literature search from 2021 till date was conducted on PakMediNet and PubMed that yielded only three clinical audit studies in Pakistan as shown in Table - 1. All these studies are closed-loop audits that follow accurate guidelines and reported significant improvement after intervention in the re-audit cycle. Ashraf M et al. reported that operative notes can be improved, by using audits to identify poor areas (3). According to Shah MH et al. standard venous thromboembolism (VTE) risk assessment and prophylactic prescription guidelines were not followed, but after intervention and re-audit, it was discovered that a simple and effective educational intervention improved VTE risk assessment and prophylactic prescribing practices (4). Similarly, Rabbani RA et al. emphasize the need for clinical audits in improving standard surgical procedures (5). No doubt that clinical audits are a tool that, when used correctly, can result in a change in the quality of care provided by a service (1). New research and clinical audit programs are crucial to the future of quality care in Pakistan (2). As a result, it is critical that our future healthcare workers understand how to conduct clinical audits and lead them during their training (2). Continuous improvement can be achieved by a healthcare unit that incorporates frequent audits with clinical practice in its curriculum. Clinical auditing will help to strengthen and increase their clinical knowledge and communication abilities. At the end of the day, it will result in improved patient care and outcomes. Therefore, the need of the hour is to promote clinical audit studies among healthcare workers.